Majas dalam Novel Bidadari-Bidadari Surga Karya Tere Liye - Susanti, Nardia; Abdurahman, Abdurahman; Nst., M. Ismail (Universitas Negeri Padang, 2013)
The purpose of this research was to describethe type and functions of figure of speech contained in the novel Bidadari-Bidadari Surgaworks Tere Liye. Based on the descriptive analysis found figure of speech hyperbole, metonymy, personification, metaphor/simile, metaphor, sinekdoke, euphemism, epipet, epanalipsis, antanaliksis, mesodiplosis, epizueksis, anaphora, sarcasm, cynicism, paradox and antithesis. The function is a figure of speech concrete, compare, smoothing, confirm, beautifying and insinuate/criticize.